Koditako Media (Digital Comics of Economic Activities) in IPAS for Fourth-Grade Students - Zulfa, Isma Alliyatuz; Bektiningsih, Kurniana (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
The use of learning media that is less varied and exciting results in students being less interested in learning, resulting in low student learning outcomes. This research aims to analyze the development, feasibility and effectiveness of Koditako media in improving student learning outcomes in the economic activities material in the science and science subject. This research is Research and Development (RnD), which refers to the ADDIE model. The subjects of this research consisted of material experts, material experts, language experts, class IV teachers and class IV students totalling 19 students. Data was collected by conducting observations, interviews, questionnaires and tests. Data analysis uses qualitative and quantitative descriptive analysis. The results of expert validation tests and teacher and student responses obtained very appropriate criteria. The T-test indicated a significant difference between the pretest and post-test average scores. The N-Gain test with moderate criteria shows increased student learning outcomes after using Koditako media. It was concluded that Koditako media is feasible and effective in improving learning outcomes for "IPAS" material on economic activities. The implication of this research is to make it easier for students to understand science learning material about economic activities so that student learning outcomes can improve.